Gamification: which elements are effective for instructional games? / Tuan Sarifah Aini Syed Ahmad, Anealka Aziz Hussin and Eliyas S. Mohandas - Syed Ahmad, Tuan Sharifah Aini; Aziz Hussin, Anealka; S. Mohandas, Eliyas (UiTM Press, 2019)
It is empirically evident that the application of gamification in instructional games has positive impacts on learning. Ahmad and Aziz (2017) revealed the potential of applying the Bloom's Taxonomy as game levels for gamifying instructional games, thus they can be used as a tool for assessment of performance for gauging students' learning progress. Borges et al. (2014) reported that studies on gamification that focus on how gamification can be utilised to boost learning, increase students' motivation and enhance students' skills. Seaborn and Fels (2014) revealed that it improves interactivity through gameful learning experience. Hamari, Koivisto, and Sarsa (2014) discovered that it has positive impacts depending greatly on the context and users in which it is applied. Stott and Neustaedter (2013) indicated that it is significant to promote engagement, but its application in education is particularly sensitive to context. Therefore, identify the right gamification elements for instructional game in order to ensure optimal learning takes place is essential.